2014
DOI: 10.1002/bip.22534
|View full text |Cite
|
Sign up to set email alerts
|

The C‐terminal calcium‐sensitive disordered motifs regulate isoform‐specific polymerization characteristics of calsequestrin

Abstract: Calsequestrin (CASQ) exists as two distinct isoforms CASQ1 and CASQ2 in all vertebrates. Although the isoforms exhibit unique functional characteristic, the structural basis for the same is yet to be fully defined. Interestingly, the C-terminal region of the two isoforms exhibit significant differences both in length and amino acid composition; forming Dn-motif and DEXn-motif in CASQ1 and CASQ2 respectively. Here, we investigated if the unique C-terminal motifs possess Ca2+-sensitivity and affect protein funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Calsequestrin, is a sarcoplamic reticulum protein of skeletal and cardiac muscle [ 38 ]. It binds 40–50 calcium ions per molecule.…”
Section: Calcium-binding Idpsmentioning
confidence: 99%
“…Calsequestrin, is a sarcoplamic reticulum protein of skeletal and cardiac muscle [ 38 ]. It binds 40–50 calcium ions per molecule.…”
Section: Calcium-binding Idpsmentioning
confidence: 99%
“…CSQ1 and CSQ2 undergo Ca 2+ -induced compaction or a shift from the proteins soluble to insoluble form [ 41 ]. CSQ1 aggregation is measured as turbidity (absorbance at 350 nm), which is proportional to the levels of insoluble CSQ1 [ 40 , 41 ]. The turbidity of WT CSQ1 increases sigmoidily across the [Ca 2+ ] range tested, reaching a constant concentration of insoluble protein at between 1 and 1.5 mM Ca 2+ (Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Solution turbidity [ 40 , 41 ] was monitored spectrophotometrically in a 1-cm path length quartz cuvette. Three micromolar protein was suspended in a buffer containing 20 mM Tris and 100 mM KCl pH 7.4.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, X-ray resolution of the human and rabbit Casq tetramer linked to Ca 2? (Kumar et al 2013) and COOH-terminal biophysical studies (Bal et al 2015) show that Casq monomer folding is not influenced by the COOH-terminal. Kumar et al (2013) also found that eight high affinity Ca 2?…”
Section: Zebrafish Calsquestrins Change Conformation In the Presence mentioning
confidence: 97%